Examination of Performance Appraisal Behavior Structure - Tziner, Aharon; Levy, Shlomit (Frontiers in Psychology, 2017)
The personality (dispositional) characteristics, attitudes, beliefs, and orientation of 498 managers and military officers toward performance appraisal and organization were collected in order to examine their structural relationships to raters' behavior, in terms of (a) mean appraisal ratings, (b) measures of performance dimensions discrimination, and (c) rate discrimination. A mapping sentence comprising a modality, a reference group, and an aspect (content) facet were used. The empirical results largely confirmed this definitional system. Moreover, a polarizing partition of the space into three regions–Self (rater), Ratee, and Organization/System–was found, possibly implying that these three considerations are equally proximal in determining rater behavior. Future directions for research are advanced.